Effects of isotopic substitution on the phonons of van der Waals crystals: the case of hexagonal boron nitride. (22nd May 2019) - Cuscó, R; Edgar, J; Liu, S; Cassabois, G; Gil, B; Artús, L
Abstract: The recent availability of isotopically pure samples of hexagonal boron nitride ( h -BN) has allowed the isotopic substitution effects to be studied in this highly interesting layered crystal. Here, we review the application of Raman scattering to investigate phonon anharmonic decay and its particularities in layered crystals, exemplified by h -BN. The modification of the phonon spectrum and anharmonic phonon decay paths in isotopically pure samples is specifically addressed. Detailed information about phonon lifetimes and decay channels is obtained for h -BN from a thorough analysis of temperature-dependent Raman scattering measurements in the light of density functional theory and perturbation theory calculations. The phonon lifetime is substantially increased in isotopically pure crystals, which may have important implications for the development of low-loss h -BN based phonon-polariton devices. On account of the low cation mass, isotopic substitution substantially alters the dominant phonon decay pathways and changes the strength of phonon anharmonic interactions.